1997
DOI: 10.1177/0145482x9709100310
|View full text |Cite
|
Sign up to set email alerts
|

The Lifestyles of Blind, Low Vision, and Sighted Youths: A Quantitative Comparison

Abstract: In this quantitative research study, 16 blind students, 16 low vision students, and 16 sighted students aged 15–21 and their parents were interviewed by telephone using questionnaires designed to examine four areas: academic involvement and performance, daily living and personal care activities, recreation and leisure activities, and work and vocational experiences. A time-diary protocol was also used to obtain data from each student in three telephone interviews during the calendar year. Similarities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 0 publications
2
42
1
8
Order By: Relevance
“…Furthermore, they experience difficulties in establishing and maintaining social, intimate and romantic relationships, which may threaten psychosocial development [ 9 12 , 18 , 19 ]. In addition, these individuals are more likely than their sighted peers (or persons with other disabilities) to live with their family after finishing school [ 20 – 22 ]. Multidisciplinary rehabilitation centers (MRCs) for the visually impaired can play a role in identifying the difficulties young adults experience, and offer guidance and rehabilitation to help overcome these difficulties [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they experience difficulties in establishing and maintaining social, intimate and romantic relationships, which may threaten psychosocial development [ 9 12 , 18 , 19 ]. In addition, these individuals are more likely than their sighted peers (or persons with other disabilities) to live with their family after finishing school [ 20 – 22 ]. Multidisciplinary rehabilitation centers (MRCs) for the visually impaired can play a role in identifying the difficulties young adults experience, and offer guidance and rehabilitation to help overcome these difficulties [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…, and for some, music is a source of personal enjoyment in their daily lives (Robb, 2003;Wolffe, Koenig, Sacks, & Lewis, 2003;Wolffe & Sacks, 1997).…”
mentioning
confidence: 99%
“…However, students with a visual impairment may need more opportunities for educationally meaningful interaction than students with sight [26][27][28][29]. Wolffe and Sacks [30] found that students with a visual impairment spend more time alone than peers with sight. Rosenblum [31] found that children with visual impairments have satisfying and supportive friendships; however, Mac-Cuspie [32] concluded as children with a visual impairment grow older, they participate less in social activities.…”
Section: Implications For Practicementioning
confidence: 99%